New records of leaf miners (Diptera Agromyzidae) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
6 species of Agromyzidae, new for Italy, are reported. The insects was collected in different areas in the past years.
Keywords: Agromyzidae; leaf miners; new records; Italy